Effect of olanzapine on laying performance of Americal king pigeons and approach to the mechanisms - ZHAO Wen-jing; GU Lin-ying; ZOU Xiao-ting; ZHANG Min; LIU Jin-guo (浙江大学学报. 农业与生命科学版)
This trial was conducted to investigate the effects and mechanism of olanzapine (a antagonist of DA and 5-HT) on laying performance of Americal king pigeons. One hundred and twenty couples of 720-day laying pigeons were randomly allocated to four groups (one control and three treatment groups), supplied with 0, 0.25, 0.75 and 1.25 mg·kg-1 olanzapine, respectively. The experiment period was sixty days. Results indicated that: 1) supplement of 0.75 and 1.25 mg·kg-1 olanzapine in diet increased the laying rate by 20.24% (P<0.05) and 23.41% (P<0.05), decreased the laying interval by 29.83% (P<0.05) and 37.46% (P< 0.05), respectively; and the serum concentrations of total protein were significantly increased by 7.33% (P< 0.05) and 11.59% (P<0.05) and blood urea nitrogen level significantly decreased by 32.6% (P<0.05) and 47.8% (P<0.05) in the 0.75 and 1.25 mg·kg-1 olanzapine groups, respectively; 2) different levels of olanzapine had no effect on fecundation and incubation rate of the eggs; compared with the control group, 0.75 and 1.25 mg·kg-1 olanzapine groups decreased prolactin concentrations by 21.90% (P<0.05) and 34.53% (P<0.05), increased the follicle-stimulating hormone concentrations by 24.0% (P<0.05) and 28.5% (P< 0.05), and increased the progestin concentrations by 33.7% (P<0.05) and 42.0% (P<0.05), respectively. It is indicated that olanzapine, as an antagonist of DA and 5-HT, can promote the laying performance of king pigeon by decreasing the prolactin concentration.